Gambaran Pengetahuan Ibu tentang Gızı Pada Balıta dı Puskesmas Karang Rejo Kota Tarakan - Asma Lanuddin; Syamsiah Syamsiah; Sari Wijayanti; Irma Novrianti (Politeknik Kaltara, 2023)
The nutritional status of toddlers is an important thing that every parent must be aware of. Nutritional problems in children under five can cause several serious impacts. Because of this nutritional problem, it can cause an inability to grow and develop cognitively and can even cause death in toddlers. This study aims to determine the level of knowledge of mothers regarding toddler nutrition. This research used a descriptive method which was carried out at the Karang Rejo Community Health Center, Tarakan City. The sample used was 97 respondents with the inclusion criteria being mothers who had babies or toddlers (aged 0-5 years) and mothers who were willing to be respondents. The research results showed that mothers' knowledge about toddler nutrition at the Karang Rejo Health Center was in the good category as many as 33 mothers (34%), in the sufficient category 57 mothers (58.8%) and in the poor category as many as 7 mothers (7.2%). It can be concluded from this study that the description of the level of knowledge of mothers regarding toddler nutrition at the Karang Rejo Community Health Center is in the sufficient category, namely 57 mothers (58.8%) out of 97 mothers.